Nucleophilic substitution in preparation and surface modification of hypercrosslinked stationary phases - Janků, Simona; Škeříková, Veronika; Urban, Jiří (Journal of chromatography. A, Including electrophoresis and other separation methods, 2015)
Four linear diaminoalkanes (1,2-diaminoethane, 1,4-diaminobutane, 1,6-diaminohexane, and 1,8-diaminooctane) have been used to hypercrosslink poly(styrene-co-vinylbenzyl chloride-co-divinylbenzene) monolithic stationary phases by nucleophilic substitution reaction. The column efficiency of polymer monoliths improved with longer diaminoalkane with 1,8-diaminoctane providing the highest efficiency. The concentration of 1,8-diaminoctane, together with hypercrosslinking time and temperature has been optimized. To improve the permeability of prepared columns, the hypercrosslinking modification has been combined with an early termination of polymerization reaction and decrease in polymerization temperature. The optimal column has been prepared by a polymerization reaction for 2h at 65°C and hypercrosslinked in the presence of 3% 1,8-diaminooctane for 2h at 95°C. The repeatability study of the presented protocol provided relative standard deviation for nine columns prepared independently out of three individual polymerization mixtures in between 2.0-12.0% for retention factors and 1.5-6.5% for plate heights, respectively. Further, we have modified residual chloromethyl groups with 2-aminoethanesulfonic acid (taurine) to prepare monolithic columns suitable for separation of small polar molecules in hydrophilic interaction chromatography. The highest retention of polar thiourea showed the column modified at 70°C for 20 h. Taurine-modified hypercrosslinked column showed the minimum of van Deemter curve of 20 μm. The prepared column provided dual-retention mechanism, including hydrophilic interaction and reversed-phase liquid chromatography that can be controlled by the composition of the mobile phase. The prepared column has been successfully used for an isocratic separation of low-molecular phenolic acids.
Keywords: Cross-Linking Reagents; reagencia zkříženě vázaná; Hydroxybenzoates; hydrofobní a hydrofilní interakce; Putrescine; Diamines; polymerizace; putrescin; Hydrophobic and Hydrophilic Interactions; Polymers; Chromatography, Reverse-Phase; hydroxybenzoáty; polymery; chromatografie s reverzní fází; diaminy; Polymerization